Enteropathogenic Escherichia coli Mediates CoCrMo Particle-Induced Peri-Implant Osteolysis by Increasing Peripheral 5-HT - Xue, Kaiwen; Tao, Ruijie; Wu, Qi; Zhang, Lei; Sun, Zhongyang; Yu, Xing; Meng, Jia; Bao, Nirong; Zhao, Jianning (Frontiers in Cellular and Infection Microbiology, 2022)
The human gut microbiota has been shown to have a great effect on bone health. However, the association between gut microbiota and particle-induced osteolysis, which is the primary cause of aseptic loosening, is still unknown. In this study, we used a combination of wide-spectrum antibiotics to eliminate the gut microbiota and examined whether the extent of osteolysis was influenced in a particle-induced osteolysis mouse model. The results demonstrated that clearance of gut commensal bacteria significantly alleviated the progression of osteolysis and the anaerobe bear the biggest responsibility in the exacerbation of osteolysis. Furthermore, we found colonization of Enteropathogenic Escherichia Coli(EPEC), a subspecies of anaerobe, could promote the development of particle-induced osteolysis by increasing the secretion of peripheral 5-hydroxytryptamine(5-HT). In mouse calvaria, 5-HT decreased the phosphorylation of CREB and downregulated the expression of Cyclin D1 and Cyclin D2. And we demonstrated that 5-HT inhibited the proliferation of osteoblast through the 5-HT1b receptor in vitro. Collectively, these results indicated EPEC colonization suppressed the proliferation of osteoblast and aggravated particle-induced osteolysis in vivo. Thus, clearance of EPEC may present a potential preventive approach to reduce debris-induced osteolysis.